Optimizing Academic Information Delivery: A Hybrid AI Chatbot Model - Isma, Andika; Fatimah Nur Arifah; Arief Zikry; Muhammad Bitrayoga; Eri Mardiani (Jurusan Teknik Informatika dan Komputer, 2024)
This research investigates the implementation of artificial intelligence (AI)-based chatbots in a hybrid model in Computer Science and Computer Engineering departments. The research method used was an online survey of students, providing direct insight from key users of this technology. The findings show significant adoption of AI chatbots in this academic environment, indicating good acceptance from users. The research results provide an in-depth understanding of the extent to which chatbots have been implemented in facilitating the reception of information in the department. AI chatbots have been proven to make a positive contribution in optimizing the process of receiving information, providing fast and accurate answers to students' common questions. The conclusions of this study underscore the potential of chatbots to improve the overall quality of academic services.